Flea-Borne Transmission Model To Evaluate Vaccine Efficacy against Naturally Acquired Bubonic Plague - Jarrett, Clayton O. (American Society for Microbiology, 2004)
A flea-to-mouse transmission model was developed for use in testing new candidate vaccines for the ability to protect against flea-borne plague. The model was used to evaluate a recombinant fusion protein vaccine consisting of the Yersinia pestis F1 and V antigens. After one to three challenges with Y. pestis-infected fleas, 14 of 15 unvaccinated control mice developed plague, with an average septicemia level of 9.2 × 10(8) Y. pestis CFU/ml. None of 15 vaccinated mice developed the disease after similar challenges, and serological testing indicated that transmitted bacteria were eliminated by the immune system before extensive replication and systemic infection could occur. The transmission and development of disease in control mice correlated with the number of bites by blocked fleas but not with the total number of fleabites. The model provides a means to directly assess the efficacy of new vaccines to prevent naturally acquired bubonic plague and to study events at the vector-host interface that lead to dissemination and disease.